Minor salivary gland mucoepidermoid carcinoma in an adolescent - A curious clinical presentation - M S Archana; Anu Babu; Geeta Sharma (Wolters Kluwer Medknow Publications, 2020)
Salivary gland tumors (SGTs) are classified as benign, malignant epithelial, soft tissue, hematolymphoid or secondary tumors. SGTs commonly affect the parotid gland and among the minor salivary glands, the hard palate is the commonest site as it harbors the highest number of salivary glands. According to various statistics, mucoepidermoid carcinoma (MEC) represents less than 0.5% of all the malignancies and less than 5% of malignant head and neck tumors. As the tumor can arise from different cells of excretory ducts these tumors often display a diverse biological behavior and unusual clinical presentation. We report a case of MEC which has a low incidence in adolescents with a rare clinical appearance.